1998
DOI: 10.1101/gad.12.20.3252
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila unpaired encodes a secreted protein that activates the JAK signaling pathway

Abstract: In vertebrates, many cytokines and growth factors have been identified as activators of the JAK/STAT signaling pathway. In Drosophila, JAK and STAT molecules have been isolated, but no ligands or receptors capable of activating the pathway have been described. We have characterized the unpaired (upd) gene, which displays the same distinctive embryonic mutant defects as mutations in the Drosophila JAK (hopscotch) and STAT (stat92E) genes. Upd is a secreted protein, associated with the extracellular matrix, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
339
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 349 publications
(353 citation statements)
references
References 52 publications
13
339
0
1
Order By: Relevance
“…Biochemical analysis of Upd revealed that the protein has an apparent molecular weight of 65 kDa, is indeed glycosylated and is localized in the extracellular matrix. Furthermore, tissue culture experi- (Harrison et al, 1998). Taken together with in vivo evidence showing that Upd functions as an activator of JAK/STAT signaling in the eye (Zeidler et al, 1999b), it is clear that Unpaired represents a bona ®de JAK/STAT pathway ligand.…”
Section: Characterization Of Drosophila Jak/stat Pathway Componentsmentioning
confidence: 98%
See 4 more Smart Citations
“…Biochemical analysis of Upd revealed that the protein has an apparent molecular weight of 65 kDa, is indeed glycosylated and is localized in the extracellular matrix. Furthermore, tissue culture experi- (Harrison et al, 1998). Taken together with in vivo evidence showing that Upd functions as an activator of JAK/STAT signaling in the eye (Zeidler et al, 1999b), it is clear that Unpaired represents a bona ®de JAK/STAT pathway ligand.…”
Section: Characterization Of Drosophila Jak/stat Pathway Componentsmentioning
confidence: 98%
“…With the recent cloning of unpaired (upd) and its identi®cation as a potential ligand for the Drosophila JAK/STAT pathway (Harrison et al, 1998), three pathway components have been identi®ed on the basis of their biochemical, genetic and mutant phenotypes.…”
Section: Characterization Of Drosophila Jak/stat Pathway Componentsmentioning
confidence: 99%
See 3 more Smart Citations